Analysis of Promethee II Method Determines The Best Cooking Oil Ayam Penyet Cindelaras Rantauprapat - Khairunnisya Ritonga; Marnis Nasution; Sahat Parulian Sitorus (Jurnal Mantik, 2021)
Cooking oil is a liquid oil made from processed plant and animal fats widely used in frying. People frequently use cooking oil to process food in order to make fried food more savoury and delicious. Every cooking oil company claims to have the best and healthiest product on the market. Cholesterol-free and contains omega 3 and 9 and vitamins A, D, and E. Decision support systems are computer programs that can solve problems based on a set of criteria. Promethee is a method used to assess the order in multi-criteria studies (priority). Simplicity, openness, and continuity are essential aspects. Promethee's parameters expected and governed by the use of partnership benefit over competitors. To users with the best substitute cooking oil breakdown, the decision support system uses the Promethee II approach. The Promethee II Template and the MCDM Model also have guidelines. Sanco oil was found in the Outrangking results, specifically Outrangking Flow 0.96, which was rated first as the best cooking oil.